Impact of atrial fibrillation on productivity in working-age patients: an analysis of Swiss-AF prospective cohort study data - Helena Aebersold; Fabienne Foster-Witassek; Sina Amberg; Miquel Serra-Burriel; Giorgio Moschovitis; Raffaele Zannoni; Stefanie Aeschbacher; Giulio Conte; Jürg H. Beer; Eva Blozik; Leo H. Bonati; David Conen; et al. (Swiss Medical Weekly)
AIMS: We aimed to explore atrial fibrillation (AF)-induced productivity losses in working-age atrial fibrillation patients and to estimate atrial fibrillation-related indirect costs.